Screening and Identification of B-Cell Epitopes in the P61 Protein of Nocardia brasiliensis - Ji, Xingzhao; Sun, Na Li; Hou, Xin Xue; Xu, Shuai; Qiu, Tong Xiao; Tang, Lu; Li, Qiao He; Wang, Bing Xue; Li, Jun Zhen (Frontiers in Cellular and Infection Microbiology, 2018)
The P61 protein is an immunodominant antigen of Nocardia brasiliensis that is observed in the sera from patients infected with the bacterium. However, the B-cell epitopes of N. brasiliensis are still unresolved. To identify the antigenic determinants of P61, we screened ten monoclonal antibodies (mAbs) against P61 protein that was expressed in the Escherichia coli system. A series of truncated peptides of P61 were then generated and the mAbs were used to screen these peptides by Western blot analyses. Three B-cell epitopes were recognized by the P61 specific mAbs: 461-FEYWTKVDPEIGKRIEEG-478, 427-LVREVFNDAQRDRLVSNVVGGVQEPV LSRVFEYWTKVDPEIGKRIEEGVRAG-482, and 447-HVLGGVQEPVLSRVFEY WTKVDPEI GKRIEEGVRAGLD-484. The latter two epitopes were further identified by N. brasiliensis-infected mouse serum. These results facilitate future investigations of serodiagnostic methods to identify Nocardia infections.